1993
DOI: 10.1080/10437797.1993.10778824
|View full text |Cite
|
Sign up to set email alerts
|

Interests, Activities, and Self-Identification Among Social Work Students

Abstract: Recent studies have suggested that the career interests of many social work students are inconsistent with the traditionally defined concept of social work identity. The current study conceptualized, operationaliz.ed, and developed measures of the prevalence of various interests, preferred activities, and self-identifications associated with social work identity among graduate social work students at the University of Toronto. Reliable dimensions of social work interests and activities were identified. Four di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 11 publications
0
20
1
2
Order By: Relevance
“…Some writers have suggested that the values and interests of social work students are inconsistent with traditionally defined concepts of social work identify (Bogo, Raphael, & Roberts, 1993). A national study of graduate social work students, however, showed that the beliefs about ''students flight from traditional social work values into entrepreneurial, private practice orientations have been overestimated.''…”
Section: Will Social Work Psychoanalysts Identify As Social Workers?mentioning
confidence: 94%
“…Some writers have suggested that the values and interests of social work students are inconsistent with traditionally defined concepts of social work identify (Bogo, Raphael, & Roberts, 1993). A national study of graduate social work students, however, showed that the beliefs about ''students flight from traditional social work values into entrepreneurial, private practice orientations have been overestimated.''…”
Section: Will Social Work Psychoanalysts Identify As Social Workers?mentioning
confidence: 94%
“…A large proportion of students (with the exception of Britain) at the beginning of their studies and upon graduation want to engage in private practice (Butler, 1990;Rubin & Johnson, 1984). Finally, regardless of the stage that students are in the socialization process or of their nationality, they express a marked preference for direct or psychotherapeutic oriented practice over engagement in social action or policy development activities (Abell & McDonell, 1990;Bogo, Raphael, & Roberts, 1993;Guttmann & Cohen, 1992).…”
Section: Research On Professional Preferencesmentioning
confidence: 98%
“…The nature of these values and norms is contested, but the definition of social work adopted by the International Federation of Social Workers and International Association of Schools of Social Work (International Federation of Social Workers, 2002) reflects a widespread consensus that a core commitment to social justice, human rights and the person-inenvironment perspective distinguish the profession (Hare, 2004). The problem is that many social work graduates choose career paths in which a commitment to social reform, structural interventions or even a combination of micro and macro practice is hard to discern (Butler, 1990;Bogo et al, 1993;D'aprix et al, 2004;Weiss et al, 2004;Weiss, 2006;Weiss-Gal, 2008). These choices may be somewhat pragmatic, but they also suggest that we could do a better job of helping social work students assume a professional identity rooted in our core values.…”
Section: Introductionmentioning
confidence: 99%
“…While this paper focuses on North America, researchers from Europe, Israel, the US and Canada have all raised concerns about social work students failing to internalize a shared sense of social work's professional mission, values and norms (Butler, 1990;Bogo et al, 1993;Barretti, 2004;D'aprix et al, 2004;Weiss et al, 2004;Weiss, 2006;Woodward and Mackay, 2011). The nature of these values and norms is contested, but the definition of social work adopted by the International Federation of Social Workers and International Association of Schools of Social Work (International Federation of Social Workers, 2002) reflects a widespread consensus that a core commitment to social justice, human rights and the person-inenvironment perspective distinguish the profession (Hare, 2004).…”
Section: Introductionmentioning
confidence: 99%